Clinico-demographic profile of women with Severe Maternal Outcomes during COVID 19 pandemic at a tertiary hospital in eastern Nepal - Basnet, Tulasa; Sitaula, Sarita; Das, Dipti; Yadav, Punita; Sah, Manoj; Shah, Deepa; Thapa, Anu; Thapa, Kamal Raj (Journal of BP Koirala Institute of Health Sciences, 2024)
Background: Severe Maternal Outcomes reflect the status of existing health care system. COVID-19 pandemic affected the healthcare delivery system and led to an increased maternal morbidity and mortality. This study aimed to assess the clinico-demographic profile of women with severe maternal outcome at B. P. Koirala Institute of Health Sciences (BPKIHS). Methods: A retrospective descriptive study was conducted at BPKIHS. Medical records of all women with severe maternal outcomes (maternal mortality and maternal near-miss) over the period of six months following lockdown (03/24/2020 - 09/24/2020), were reviewed. Maternal near-miss cases were identified as per ‘a specific intervention-based criteria’ defined by World Health Organization (WHO). The demographic and clinical variables of interest were recorded and analyzed. Results: There were 97 cases of severe maternal outcomes; 18 maternal mortalities and 79 maternal near-miss. Severe Maternal Outcome incidence ratio (SMOR) was 22.61/1000 live births, Maternal Near-Miss incidence ratio (MNMR) was 18.4/1000 live births and the Maternal Mortality Ratio (MMR) was 419 per 100,000 live births. The mean age was 27.93 ± 7.67 years. Major causes of severe maternal outcomes were obstetric hemorrhage (48.45%), sepsis (18.56%) and hypertensive disorders (16.49%). The leading cause of mortality was sepsis (27.78%) followed by hypertension and obstetric hemorrhage. COVID-19 infection was responsible for 5.56% of maternal mortality. Conclusions: Severe maternal outcome ratio and maternal mortality remained high during COVID-19 pandemic. Obstetric hemorrhage, sepsis, and hypertensive disorders are the leading causes of adverse maternal outcomes with COVID-19 affecting the outcome both directly and indirectly.